Analysis of Strategic Capabilities Based on the VRIO Framework Among Chinese EV Manufacturers in Complying with Indonesia’s TKDN Regulations: A Case Study of BYD and Wuling - Herawan, Deni; YP, Kristianto Didit; Agustian, Deni; Purnamasari, Pupung (Journal Research of Social Science, Economics, and Management, 2026)
Indonesia’s Tingkat Komponen dalam Negeri (TKDN) regulation mandates that four-wheeled battery electric vehicles achieve progressively increasing local content, targeting 80% by 2030. Yet aggregate Indonesian BEV output reached only 9,847 units in 2023 approximately 0.5% of internal combustion engine production with adoption remaining near 1% of the 2030 target by September 2024. This study applies quantified VRIO to identify, score, and compare BYD and Wuling’s strategic resources across Value, Rarity, Inimitability, and Organization within Indonesia’s 80% TKDN threshold addressing a gap in prior research on EV incentives, consumer barriers, and sectoral challenges. This qualitative multiple-case study examined BYD and Wuling the two largest Chinese BEV investors in Indonesia using quantified VRIO across four dimensions: Value, Rarity, Inimitability, and Organization. Data are triangulated from annual reports, TKDN records, investment disclosures, and regulatory documents (2019–2024). The empirical findings reveal that both firms score equivalently on Value (4/5), yet their binding constraints diverge sharply. Wuling’s lowest score is Inimitability (2/5), reflecting an underdeveloped local supplier ecosystem for critical BEV components that exposes its entry-level product positioning to replication. BYD’s lowest score is Organization (2/5), reflecting a pre-operational Indonesian footprint where governance routines and supplier-liaison capacity remain unverified despite globally rare technology capabilities. Neither firm satisfies the joint VRIO condition required for sustained competitive advantage under the resource-based view but the remediation pathway differs systematically: Wuling requires supplier ecosystem development, while BYD requires organizational scaffolding installation.